A rare variant of transthyretin-related amyloidosis associated with exclusive cardiomyopathy in a Hong Kong Chinese patient. Issue 6 (December 2018) - Wong, Chi Wing; Ng, Wai Yan; So, Ka Li; Chan, Yu Ho; Yip, Sze Fai; Mak, Chloe Miu
Abstract: Hereditary transthyretin-related amyloidosis (ATTR, MIM #105210), also previously known as familial amyloidotic polyneuropathy, is one of the most life-threatening types of amyloidosis. ATTR is inherited in autosomal dominant mode with variable penetrance. If untreated, it is a relentless and lethal disease. Patients typically present with polyneuropathy, carpal tunnel syndrome, autonomic insufficiency, cardiomyopathy, and gastrointestinal features, occasionally accompanied by vitreous opacities and renal insufficiency. Frequency of transthyretin (TTR)-related cardiac amyloidosis amongst Chinese populations is unknown. We report here a 63-year-old Chinese man suffering from TTR-related cardiac amyloidosis presented with exclusive cardiomyopathy. He had no other systemic involvement and no significant family history. Echocardiography revealed severe global myocardial impairment and left ventricular ejection fraction of 35%. Serum kappa-to-lambda ratio was normal. Genetic test detected a heterozygous TTR variant, NM_000371.3:c.425T > C p.(Val142Ala). To our knowledge, this is the first case of TTR-related cardiac amyloidosis caused by p.Val142Ala mutation reported in Asian patient. <Learning objective: This case highlights the importance to exclude transthyretin-related cardiac amyloidosis as a cause of extensive cardiomyopathy, despite the late disease onset and lack of systemic amyloidosis. High clinical suspicion and genetic testing is the key for early diagnosis.>